2020
DOI: 10.1186/s12931-020-1322-5
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 inhibitor attenuates airway responses to antigen stimulus through synchronously suppressing galectin-3 expression and reducing macrophage-2 polarization

Abstract: Background: This study was to investigate of the mechanism by which histone deacetylase (HDAC) 8 inhibitor ameliorated airway hyperresponsiveness (AHR) and allergic airway inflammation. Methods: Mice were sensitized and then treated with budesonide (BUD) or PCI-34051 (PCI) prior to exposing to normal saline (NS) or ovalbumin (OVA). The raw264.7 cells were treated with interleukin (IL)-4 and PCI or shRNA alone. Repetitive measurements of enhanced pause (Penh) were executed by increasing concentrations of acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…HDAC8 has been shown to have increased enzymatic activity and play a pathogenic role in pulmonary asthma; when mice in a model of allergic asthma were exposed to ovalbumin (OVA), the level of HDAC8 protein expression was significantly increased in the lungs, together with high numbers of CD68 and CD163 macrophages. Treatment with the specific HDAC8 inhibitor PCI-34051 reduced these effects [32]. Another study found that PCI-34051 downregulated inflammatory cytokines in peripheral blood mononuclear cells (IL-18, IL-1b, MIP-1b, MCP-1, TNFa and IL-6) [33].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC8 has been shown to have increased enzymatic activity and play a pathogenic role in pulmonary asthma; when mice in a model of allergic asthma were exposed to ovalbumin (OVA), the level of HDAC8 protein expression was significantly increased in the lungs, together with high numbers of CD68 and CD163 macrophages. Treatment with the specific HDAC8 inhibitor PCI-34051 reduced these effects [32]. Another study found that PCI-34051 downregulated inflammatory cytokines in peripheral blood mononuclear cells (IL-18, IL-1b, MIP-1b, MCP-1, TNFa and IL-6) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacyclic’s PCI-34051 ( 52 , Figure ) was the first to exhibit high selectivity for HDAC8 and is the most widely used tool compound for this isoform . Newer examples include Huang’s cinnamoyl terphenylhydroxamic acid WK2-16 ( 53 ) and Beeler’s phenylalanine derived hydroxamic acid 54 . , In animal models, selective HDAC8 inhibitors have shown promise in neuroblastoma as well as different inflammatory settings such as hypertensive inflammation, neuroinflammation, and airway inflammation . Recently, 52 was shown to resensitize melanoma tumor xenograft cells to inhibition by the tyrosine kinase inhibitor erlotinib …”
Section: Isoform Selectivitymentioning
confidence: 99%
“…Indeed, we performed independent experiments using cell-free assays indicating that LSF did not inhibit any of the other metal-dependent HDAC enzymes at biologically relevant concentrations (mM range for HDAC3, HDAC6, and HDAC7 and undetectable for others). This is an interesting observation as it has been previously shown that a potent specific HDAC8 inhibitor (PCI-34501), attenuated airway responses in OVA-sensitized mice 59 .…”
Section: Our Findings Indicated Reductions Of Inflammatory Infiltrate...mentioning
confidence: 52%